2007
DOI: 10.1364/oe.15.009357
|View full text |Cite
|
Sign up to set email alerts
|

Strong luminescence from strain relaxed InGaN/GaN nanotips for highly efficient light emitters

Abstract: Semiconductor heterostructures represent the most important building block for current optoelectronic devices. One of the common features of semiconductor heterostructures is the existence of internal strain due to lattice mismatch. The internal strain can tilt the band alignment and significantly alter the physical properties of semiconductor heterostructures, such as reducing the internal quantum efficiency of a light emitter. Here, we provide a convenient route to release the internal strain by patterning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12] The fabrication method has typically involved "top-down" patterning by etching an initially planar epitaxial structure containing InGaN/GaN QWs, although studies of directly grown nano-columnar structures have also been reported. 12 Correlations between spectroscopic results and numerical simulations of strain relaxation in the QWs were included in the reports by Yu et al 9 and Kawakami et al 10 The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] The fabrication method has typically involved "top-down" patterning by etching an initially planar epitaxial structure containing InGaN/GaN QWs, although studies of directly grown nano-columnar structures have also been reported. 12 Correlations between spectroscopic results and numerical simulations of strain relaxation in the QWs were included in the reports by Yu et al 9 and Kawakami et al 10 The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This blue-shift may be induced by reduction of the piezoelectric field caused by strain relaxation. 42 The PL full-width-half-maximum (FWHM) is narrower for the thick buffer structure (600 nm) than for the other structures, for both AlGaN/GaN and InAlN/GaN-based heterostructures. Results from comparative analysis of the different characteristics of the RT-PL peaks of the AlGaN/ GaN and InAlN/GaN-based heterostructures are shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It can make carriers bound and reduce the capture probability of unirradiative recombination centre, luminescence efficiency has been enhanced. In general, even though InGaN/GaN MQWs has bigger dislocation density, it has higher luminescence quantum efficiency [5]. Therefore, In-composition fluctuation and phase separation are significant.…”
Section: Resultsmentioning
confidence: 99%